Effect of fat combinations on starter pig performance and nutrient digestibility - Li, D.F.; Harmon, D.L.; Fitzner, G.E.; Jones, D.B.; Nelssen, Jim L.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A growth trial was conducted to evaluate the effects of addition of soybean oil, coconut oil, 50% soybean oil: 50% coconut oil, 75% soybean oil: 25% coconut oil, and 25% soybean oil: 75% coconut oil on starter pig performance and nutrient digestibility. Diets were supplemented with 10% fat for the first 2 wk of the study and 5% for the final 3 wk. Fecal samples were collected from pigs by rectal massage, and apparent digestibility of DM, N, total fat, and fatly acids were calculated using chromic oxide (.3%) as an indigestible marker. Results demonstrated that ADG and feed efficiency (F/G) were improved by fat additions, with 50% soybean oil and 50% coconut oil maximizing performance. Pigs gained faster on the soybean oil and coconut oil combinations than on coconut oil and consumed more of the soybean oil plus coconut oil diet than either coconut oil or soybean oil diets. No differences were observed for apparent digestibility of fat and GE or ileal digestibility of DM and N among the fat sources. However, pigs fed the combination of soybean oil and coconut oil tended to have improved ileal digestibility of medium chain fatty acids (< 14 C). These trials demonstrate that a combination of soybean oil and coconut oil improves pig performance and tends to improve apparent digestibility of medium chain fatty acid compared to pigs fed diets containing either no added fat or soybean oil or coconut oil alone.
Keywords: Swine; Pig; Digestibility; Fat; Performance